Revisiting the Conceptual Aspects of Humanization and Dignified Treatment in Healthcare from an Ethical Perspective: A systematic review of the literature - Andreucci-Annunziata, Paola; Mellado, Augusto; Vega-Muñoz, Alejandro; León-Correa, Francisco (Acta Bioethica, 2024)
Background: The attainment of humanization and dignified treatment in healthcare has proven to be a challenging endeavor, notwithstanding the advancements made in initiatives aimed at their implementation. One approach to addressing this issue is to direct reflection towards its ethical and conceptual foundations, as well as exploring the potential integration of the various dimensions involved in its management and approach. Objectives: The aim of this study is to conduct a systematic review of original articles focusing on humanization and dignified treatment in healthcare from an ethical and bioethical standpoint, with two specific research objectives: 1. To identify key conceptualizations related to humanization and dignified treatment, taking into account the perspectives of the various stakeholders at contextual, institutional, interpersonal, and personal levels. 2. To propose a relational model that facilitates the visualization of the dimensions, agents, and practices involved in humanization. Methods: A systematic search was performed in the Web of Science (WoS) database, following bibliometric procedures and the PRISMA methodology. Results: A total of 8 articles were selected from the WoS indexing categories of “Ethics” and “Religion,” published between 2010 and 2022. The analysis revealed that ethics and bioethics play a fundamental role in shaping the discourse on humanization and dignified treatment in healthcare. Key themes included respect for individuals’ integrity, relational ethics, associated ethical principles, and concrete institutional practices. Discussion: The implications of considering ethical notions as foundations for humanization and dignified treatment in healthcare, as well as the proposal of a relational model in humanization applicable to healthcare practices, are discussed.